The Effect of Multimedia Based Learning in Chemistry Teaching and Learning on Students’ Self-Regulated Learning - Erfan Priyambodo; Sulistyani Sulistyani (Journal of Education and Learning (EduLearn), 2014)
In recent years, the uses of Multimedia Based Learning (MBL) in classroom instruction increased widely. Overall, this implementation aims to improve students’ motivation and also their learning outcomes. This study was answering the effect of MBL toward students’ Self-Regulated Learning (SRL) in chemistry teaching and learning. The experiment was conducted in class XI of senior high school in Yogyakarta. Researchers create some computer based media for chemistry materials and continued with expert judgement of the media. Students’ data SRL were measured using validated questionnaire. The questionnaire consists of three components, i.e. metacognitive, motivation and behavior. The results showed that there was significant differences in SRL of students before and after participating in chemistry teaching and learning which applying MBL.